PENDIDIKAN KARAKTER CINTA TANAH AIR DALAM PEMBELAJARAN PENDIDIKAN PANCASILA SMP N 43 SEMARANG - Fifin, Novita; Purwosaputro, Supriyono; Widodo, Suwarno (Civis : Jurnal Ilmiah Ilmu Sosial dan Pendidikan, 2023)
This study was carried out with the fact that students did not optimally understand the importance of loving the homeland, there were still many students who did not take part in the flag ceremony solemnly, there were still notes of violations from the students themselves (such as when the teacher was teaching there were still some children talking to themselves, there were still some children who had not used the full attributes, especially class VII, namely the class marks for the student council). This research is intended as a form of knowledge about the application of the character of loving the motherland. This researcher uses a qualitative descriptive method. Data collection techniques were carried out by observation, interviews, and documentation. This research produced information on the application of the character of love for the motherland in learning Pancasila education for class VII students of SMP N 43 Semarang. In this study, it is in accordance with the indicators of love for the motherland, namely the implementation of the application of love for the motherland in learning Pancasila Education inside and outside of learning. However, the implementation process still has deficiencies, namely the students' knowledge that is not yet optimal regarding character education for loving the motherland. Also, there are several factors that hinder its implementation, namely students from different backgrounds. That way the teacher must be committed to increasing students' understanding of character education for loving the motherland. The existence of several inhibiting factors is a challenge for the teacher